واقع أنظمة ضمان الجودة في الصناعة العراقية: دراسة استطلاعية - د. محفوظ حمدان الصواف; ليلى مصطفى محمـد بــلال (PROSPECTIVE RESEARCHES, 2023)
The study dealt real quality systems in Iraqi industry through a field systemic survey to capture the reality of systems and their fundamental bases represented by its status, structure, and activities. The study sought too, to answer the following questions. 1. Is there a recognition to the need for establishing or developing a system for ensuring quality? 2. Are these systems viewed as suitable instruments to continue improvement ? 3. What are the most probable factors that aid in establishing systems for ensuring quality ? The study concluded the main physical bases to construct a quality system is existed with respect to Iraqi industry, but they are scattered so there is a need to a radical review in establishing physical and human bases according to a new developed system toward enhancing the competitive position and satisfying the customer. The study concluded with a set of necessary recommendations and suggestions for the sample firms of the study.